Sistem dan Prosedur Administrasi Persuratan di Bagian Pelelangan PT Bank Tabungan Negara (Persero) Tbk KC Palembang - Indah Purnama Sari; Diana Widhi Rahmawati; Hendri Gunawan (Politeknik Kampar, 2026)
This study aims to analyze the system and procedures of administrative correspondence in the auction department of PT Bank Tabungan Negara (Persero) Tbk KC Palembang. The research uses a descriptive qualitative approach, with data collection through field observation during a three-month internship, documentation review of auction-related letters, and interviews with administrative staff and unit heads. The results indicate that the correspondence system at BTN KC Palembang is well-structured but still faces several obstacles, including bureaucratic bottlenecks in the letter disposition process, reliance on manual archiving systems, human errors in data entry, and logistical challenges in external communication with institutions such as KPKNL Palembang. These obstacles affect the efficiency and timeliness of the auction process, which in turn impacts asset recovery (recovery) and bank cash flow. The study concludes that digital transformation—such as implementing e-filing, digital tracking systems, and standard templates—is the most effective solution to improve administrative efficiency and legal certainty in the auction process.